Important performance factors in gymnastics from a biomechanical perspective - Prassas, S. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Perhaps more than in any other sport, success in gymnastics depends on the ability of the athlete to blend a variety of physical, physiological, and psychological attributes in a routine that taxes the body and mind. Without denying the importance of physiological, psychological, and other variables, this paper (based on Prassas et al., 2006) will discuss performance variables important in putting together a winning gymnastics routine from a biomechanical perspective.